Fixed rehabilitation of patient with aggressive periodontitis using zygoma implants. - Rajan, G.; Baig, M.R.; Nesan, J.; Subramanian, J. (2010)
Treatment of patients with aggressive periodontitis has always been a challenge to the clinician. Both young and old are known to be affected by this progressive destructive condition of the supporting dental structures. Although dental implants have been offered as a viable treatment alternative for such patients, additional procedures (like bone grafting) and delayed protocols have limited their usage. This case report describes the treatment of a young patient with aggressive periodontitis using a graftless implant solution. Zygoma implants in conjunction with conventional implants were used with immediate loading.